2006
DOI: 10.1111/j.1471-4159.2006.03652.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of taurine transport in rat hippocampal neurons by hypo‐osmotic swelling

Abstract: Taurine, an important mediator of cellular volume regulation in the central nervous system, is accumulated into neurons and glia by means of a highly specific sodium-dependent membrane transporter. During hyperosmotic cell shrinkage, net cellular taurine content increases as taurine transporter activity is enhanced via elevated gene expression of the transporter protein. In hypo-osmotic conditions, taurine is rapidly lost from cells by means of taurine-conducting membrane channels. We reasoned that changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 86 publications
4
19
1
Order By: Relevance
“…Previous studies have indicated that during episodes of hypoosmotic stress organic osmolyte homeostasis is regulated not only via osmolyte efflux but also at the level of osmolyte reuptake (Olson and Martinho, 2006;Foster et al, 2009). Consistent with this possibility, a major finding from the present study is that mAChR-mediated uptake of Daspartate (and to a lesser extent, basal uptake) is significantly attenuated when SH-SY5Y cells are subjected to hypoosmotic stress.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have indicated that during episodes of hypoosmotic stress organic osmolyte homeostasis is regulated not only via osmolyte efflux but also at the level of osmolyte reuptake (Olson and Martinho, 2006;Foster et al, 2009). Consistent with this possibility, a major finding from the present study is that mAChR-mediated uptake of Daspartate (and to a lesser extent, basal uptake) is significantly attenuated when SH-SY5Y cells are subjected to hypoosmotic stress.…”
Section: Discussionsupporting
confidence: 79%
“…Second, the lack of change in the net content of amino acids other than taurine and alanine may be a result of rapid reuptake into adjacent glial cells or into the neurons from which they were released. Although taurine also is known to be accumulated by neurons and glial cells (6,32,33,71), we found that ATP did not alter unidirectional uptake of taurine into the neuron cultures. Conversely, the broadly acting P2 receptor antagonist suramin increased the rate of taurine accumulation.…”
Section: Discussioncontrasting
confidence: 55%
“…With our methods, these primary cultures of rat hippocampal neurons contained ϳ20% astroglial cells as defined by counts of glial fibrillary acidic protein (GFAP)-positive cells and the specific activity of the astrocyte-specific enzyme glutamine synthetase (71). All cells used in these studies were neurons as defined by their general morphological appearance and the presence of inward currents observed upon membrane depolarization; however, the specific neuronal cell type was not characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The taurine transporter (TauT) belongs to the β-amino acid transport system [10][11][12] . This system is specific for taurine and other β-amino acids, such as β-alanine and hypotaurine [13] .…”
mentioning
confidence: 99%